How not to get squeezed [patent battle]. - Gardella, G.H (IEEE spectrum)
This article briefly discusses five lessons to be learned from the ongoing patent battle over the BlackBerry wireless e-mail system between RIM and NTP. Unless RIM, based in Waterloo, Ont., Canada, negotiates a settlement with NTP regarding the infringement of five NTP patents, RIM could be barred from operating its network in the United States.